Pengembangan Sistem Informasi Persediaan Barang dan Transaksi Penjualan (Studi Kasus Agen Snack SSS) - Wahyu Rizki Ananta; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
SSS Snack Agent is a small business engaged in the wholesale trade of snacks and beverages. Currently, the recording of inventory and sales transactions is still done manually, resulting in limited access to information and the risk of miscalculation or recording. In addition, checking expired goods is quite difficult for employees because there is no record of the expiration date of goods when received from distributors. In response to these problems, the solution offered is to develop an inventory information system and sales transactions to make it easier for employees to solve problems related to recording inventory and sales transactions, as well as checking expired goods. The system will be developed with a waterfall on a web system with codeigniter framework based on the PHP programming language. The steps taken include needs analysis, design, implementation, and testing. The results of the validation test get 100% valid results from 11 test cases. For the results of the user acceptance testing (UAT), the test was carried out on three actors. First, the owner actor with a UAT percentage value of 81%; second, the cashier actor with a UAT percentage value of 82.5%; and finally, the warehouse staff actor with a UAT percentage value of 84%.